A silicon-carbon composite negative electrode material and its preparation method and application
By doping metal lithium into the core of silicon carbon material and coating lithium sulfonate, the problem of insufficient power performance and first-time efficiency of silicon carbon negative electrode material is solved, and a significant improvement in material performance and excellent performance of lithium-ion batteries are achieved.
Patent Information
- Application Number
- CN202411045796.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-01
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-08-01
AI Technical Summary
The power performance and first-time efficiency of existing silicon-carbon anode materials are insufficient, and the poor electronic conductivity and high specific surface area of porous carbon lead to material performance deviations.
By doping metal lithium into the core of silicon carbon material and coating the surface with lithium sulfonate, the electronic conductivity and lithium ion conductivity of the material are improved, thereby improving power performance and first-time efficiency.
It significantly improves the power performance and first-time efficiency of silicon-carbon composite anode material, improves rate performance and storage performance, and the prepared lithium-ion battery has excellent performance.
Smart Images

Figure CN118572094B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and specifically relates to a silicon-carbon composite negative electrode material and a preparation method and application thereof. Background Art
[0002] As the market demand for high energy density batteries increases, the negative electrode materials used in lithium-ion batteries are required to have high specific capacity and high initial efficiency, while the power performance of the materials should also be improved. The silicon-carbon material prepared by the silane cracking method is composed of porous carbon and its deposition on nano-silicon, and amorphous carbon is coated on its surface, thereby reducing gas production and improving the initial efficiency. However, due to the poor electronic conductivity of the porous carbon itself and its high specific surface area, the initial efficiency and power performance of the material are deviated, and the single coating of amorphous carbon in the outer shell only slightly improves the electronic conductivity of the material, but does not improve the ionic conductivity and transmission rate of the material, resulting in a deviation in the power performance of the material.
[0003] Therefore, how to effectively improve the power performance and initial efficiency of silicon-carbon negative electrode materials is a technical problem that needs to be solved urgently. Summary of the invention
[0004] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a silicon-carbon composite negative electrode material and a preparation method and application thereof. The present invention not only effectively reduces the irreversible capacity of the silicon-carbon composite negative electrode material by doping metallic lithium in the inner core, but also improves the electronic conductivity and the first efficiency of the silicon-carbon composite negative electrode material; and by coating lithium sulfonate on the surface of the inner core, on the one hand, the lithium ion conductivity and diffusion rate of the material are improved, and the power performance and the first efficiency of the material are improved. On the other hand, lithium sulfonate has good compatibility with electrolyte solvents, which significantly improves the rate performance and storage performance of the material. The lithium-ion battery prepared in this way has excellent power performance and high first efficiency.
[0005] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0006] In a first aspect, the present invention provides a silicon-carbon composite negative electrode material, which includes a lithium-doped silicon-carbon material core and a coating layer coated on the surface of the core, wherein the material of the coating layer includes lithium sulfonate.
[0007] The present invention not only effectively reduces the irreversible capacity of the silicon-carbon composite negative electrode material by doping metallic lithium in the core, but also improves the electronic conductivity and first efficiency of the silicon-carbon composite negative electrode material; and by coating lithium sulfonate on the surface of the core, on the one hand, the lithium ion conductivity and diffusion rate of the material are improved, and the power performance and first efficiency of the material are improved. On the other hand, lithium sulfonate has good compatibility with electrolyte solvents, which significantly improves the rate performance and storage performance of the material. The lithium-ion battery prepared in this way has excellent power performance and high first efficiency.
[0008] Preferably, the lithium-doped silicon-carbon material core is a porous structure.
[0009] In the present invention, the porous core is doped with metallic lithium, which is beneficial to reducing defects and improving electronic conductivity. In addition, the presence of the holes also provides space for the expansion of silicon during charging and discharging, thereby reducing expansion.
[0010] Preferably, the doping amount of lithium in the lithium-doped silicon-carbon material core is 1-5wt%, for example, it can be 1wt%, 2wt%, 3wt%, 4wt% or 5wt%.
[0011] In the present invention, if the doping amount of lithium is too little, the improvement of the electronic conductivity and the first efficiency of the material is limited; if the doping amount of lithium is too much, the residual alkali of the material is too high, the pH value is increased, and the processing performance is reduced.
[0012] Preferably, the lithium-doped silicon-carbon material core is further doped with heteroatoms, and the heteroatoms include nitrogen atoms.
[0013] In the present invention, the doping of heteroatoms is beneficial to increase electron holes and increase electronic conductivity.
[0014] Preferably, the coating layer has a thickness of 50-500 nm, for example, 50 nm, 100 nm, 200 nm, 300 nm, 400 nm or 500 nm.
[0015] In the present invention, if the thickness of the coating layer is too small, the coating integrity of the material is limited, the gas production is limited, and the ionic conductivity of the material is limited; if the thickness of the coating layer is too large, the specific capacity of the material will be significantly reduced.
[0016] In a second aspect, the present invention provides a method for preparing the silicon-carbon composite negative electrode material as described in the first aspect, the preparation method comprising the following steps:
[0017] (1) preparing a carbon material, and then sequentially introducing a lithium source gas and a silicon source gas into a reaction device where the carbon material is located to obtain a lithium-doped silicon-carbon precursor material;
[0018] (2) The lithium-doped silicon-carbon precursor material, lithium sulfonate and an organic solvent are mixed and dried to obtain the silicon-carbon composite negative electrode material.
[0019] Preferably, the carbon material in step (1) is a porous carbon material doped with heteroatoms.
[0020] In the present invention, heteroatom doping of the porous carbon material is beneficial to improving the electronic conductivity.
[0021] Preferably, the steps of preparing the heteroatom-doped porous carbon material include:
[0022] The template, the heteroatom compound, the phenolic compound, the aldehyde compound and the alcohol organic solvent are mixed and reacted, and then activated and carbonized to obtain the heteroatom-doped porous carbon material.
[0023] In the present invention, the purpose of activation is to form pores, thereby preparing porous carbon; the purpose of carbonization is to increase the strength of the pore structure and obtain a pore volume of appropriate size.
[0024] Preferably, the template includes any one of zinc chloride, zinc bromide, lithium chloride or lithium bromide, or a combination of at least two of them.
[0025] Preferably, the heteroatom compound includes any one of urea, melamine or dopamine, or a combination of at least two of them.
[0026] Preferably, the phenolic compound includes any one of phenol, hydroquinone, catechol or p-tert-butylphenol, or a combination of at least two thereof.
[0027] Preferably, the aldehyde compound includes any one of formaldehyde, acetaldehyde, benzaldehyde, phenylacetaldehyde, phenylpropionaldehyde or cinnamaldehyde, or a combination of at least two thereof.
[0028] Preferably, the alcohol organic solvent includes any one of ethanol, methanol or ethylene glycol, or a combination of at least two of them.
[0029] Preferably, the mass ratio of the template, heteroatom compound, phenolic compound and aldehyde compound is (1-5):(1-5):100:(100-200), wherein the selection range of the template "1-5" can be, for example, 1, 2, 3, 4 or 5, the selection range of the heteroatom compound "1-5" can be, for example, 1, 2, 3, 4 or 5, and the selection range of the aldehyde compound "100-200" can be, for example, 100, 120, 140, 160, 180 or 200, etc.
[0030] In the present invention, if the amount of the heteroatom compound used is too small, the electronic conductivity of the material will be limited; if the amount of the heteroatom compound used is too large, the tap density of the material will be reduced.
[0031] Preferably, the reaction temperature is 150-250°C, such as 150°C, 200°C or 250°C, and the reaction time is 6-12h, such as 6h, 8h, 10h or 12h.
[0032] In the present invention, if the reaction temperature is too low, the reaction process will be slowed down; if the reaction temperature is too high, the solvent will volatilize and the formed phenolic resin will have poor structural density.
[0033] Preferably, carbon dioxide gas is introduced during the activation process.
[0034] Preferably, the activation temperature is 500-800°C, for example, 500°C, 600°C, 700°C or 800°C, and the activation time is 1-6h, for example, 1h, 2h, 3h, 4h, 5h or 6h.
[0035] Preferably, the atmosphere of the carbonization treatment is an inert atmosphere.
[0036] It should be noted that the present invention does not limit the gas in the inert atmosphere, and illustratively, it may be argon gas, etc.
[0037] Preferably, the carbonization treatment temperature is 1100-1500°C, for example, 1100°C, 1200°C, 1300°C, 1400°C or 1500°C, and the time is 1-6h, for example, 1h, 2h, 3h, 4h, 5h or 6h.
[0038] Preferably, the lithium source gas in step (1) comprises lithium hydride gas.
[0039] It should be noted that lithium hydride is a white crystalline powder at room temperature and needs to be heated to 850-950°C to be converted into lithium hydride gas.
[0040] Preferably, the flow rate of the lithium source gas in step (1) is 50-200 mL / min, for example, 50 mL / min, 100 mL / min, 150 mL / min or 200 mL / min.
[0041] Preferably, the lithium source gas is introduced into the reaction vessel for 30-300 min, for example, 30 min, 50 min, 100 min, 150 min, 200 min, 250 min or 300 min.
[0042] Preferably, the silicon source gas in step (1) is chlorosilane gas.
[0043] In the present invention, chlorosilane gas is used to deposit nano-silicon, which has the advantages of high safety performance and low price compared with silane gas. In addition, since chlorosilane gas has residual chlorine atoms doped after cracking, it is beneficial to improve the electronic conductivity of the material.
[0044] Preferably, the chlorosilane gas includes any one of trichlorosilane, tetrachlorosilane, dichlorosilane, methyldichlorosilane, methylchlorosilane, tripropylchlorosilane, dimethylchlorosilane or propyltrichlorosilane gas, or a combination of at least two thereof;
[0045] Preferably, the flow rate of the silicon source gas in step (1) is 100-500 mL / min, for example, it can be 100 mL / min, 200 mL / min, 300 mL / min, 400 mL / min or 500 mL / min.
[0046] Preferably, the silicon source gas is introduced into the reaction vessel for 120-600 min, for example, 120 min, 150 min, 200 min, 300 min, 400 min, 500 min or 600 min.
[0047] Preferably, in step (2), the mass ratio of the lithium-doped silicon-carbon precursor material to the lithium sulfonate is 100:(5-20), for example, it can be 100:5, 100:10, 100:15 or 100:20.
[0048] In the present invention, if the mass ratio of the lithium-doped silicon-carbon precursor material and the lithium sulfonate is too small, that is, the amount of lithium sulfonate used is too much, the specific capacity of the silicon-carbon material will be reduced; if the mass ratio of the lithium-doped silicon-carbon precursor material and the lithium sulfonate is too large, that is, the amount of lithium sulfonate used is too small, the improvement in the ionic conductivity and the first efficiency of the material will be too small.
[0049] Preferably, the lithium sulfonate includes any one of lithium perfluorohexane sulfonate, lithium trifluoromethane sulfonate, lithium perfluorobutyl sulfonate or lithium dodecane sulfonate, or a combination of at least two thereof.
[0050] Preferably, the specific steps of mixing in step (2) include:
[0051] Lithium sulfonate is added to an organic solvent to obtain a lithium sulfonate solution, and then a lithium-doped silicon-carbon precursor material is added and mixed.
[0052] Preferably, the organic solvent comprises any one of methyl propionate, ethyl acetate, diethyl carbonate, ethyl methyl carbonate or dimethyl carbonate, or a combination of at least two thereof.
[0053] Preferably, the mass fraction of the lithium sulfonate solution is 1-10wt%, for example, it may be 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%.
[0054] Preferably, the drying method in step (2) includes spray drying.
[0055] Preferably, the preparation method comprises the following steps:
[0056] (1) adding a phenolic compound and an aldehyde compound to an alcohol organic solvent and dispersing them uniformly to obtain a solution with a mass fraction of 1-10 wt%, then adding a template and a heteroatom compound to mix, and then transferring to a high-pressure reactor at 150-250° C. for 6-12 hours of reaction, filtering, and then activating the obtained filter residue at a temperature of 500-800° C. for 1-6 hours, while introducing carbon dioxide gas at a flow rate of 50-200 mL / min, and after activation, carbonizing in an inert atmosphere at 1100-1500° C. for 1-6 hours to obtain a heteroatom-doped porous carbon material;
[0057] Wherein, the mass ratio of the template agent, the heteroatom compound, the phenolic compound and the aldehyde compound is (1-5):(1-5):100:(100-200);
[0058] (2) transferring the heteroatom-doped porous carbon material to a tube furnace, evacuating the furnace, and then introducing a lithium source gas at a flow rate of 50-200 mL / min, and maintaining the pressure in the furnace at 0.1-0.5 MPa for 30-300 min, and then changing to a silicon source gas at a flow rate of 100-500 mL / min for 120-600 min to obtain a lithium-doped silicon-carbon precursor material;
[0059] (3) adding lithium sulfonate to an organic solvent to obtain a lithium sulfonate solution with a mass fraction of 1-10 wt%, then adding the lithium-doped silicon-carbon precursor material to disperse uniformly, and spray drying to obtain a silicon-carbon composite negative electrode material;
[0060] Wherein, the mass ratio of lithium-doped silicon-carbon precursor material to lithium sulfonate is 100:(5-20).
[0061] In a third aspect, the present invention provides a negative electrode plate, wherein the negative electrode plate comprises the silicon-carbon composite negative electrode material as described in the first aspect.
[0062] In a fourth aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the negative electrode sheet as described in the third aspect.
[0063] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0064] Compared with the prior art, the present invention has the following beneficial effects:
[0065] The present invention not only effectively reduces the irreversible capacity of the silicon-carbon composite negative electrode material by doping metallic lithium in the core, but also improves the electronic conductivity and the first efficiency of the silicon-carbon composite negative electrode material; and by coating lithium sulfonate on the surface of the core, on the one hand, the lithium ion conductivity and diffusion rate of the material are improved, and the power performance and the first efficiency of the material are improved. On the other hand, lithium sulfonate has good compatibility with the electrolyte solvent, which significantly improves the rate performance and storage performance of the material. The lithium-ion battery prepared in this way has excellent power performance and high first efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0066] Figure 1 This is a DC internal resistance distribution diagram of the soft-pack battery made of the silicon-carbon composite negative electrode material provided by Examples 1-3, Example 7 and Comparative Example 1 of the present invention under different SOC states. DETAILED DESCRIPTION
[0067] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0068] Example 1
[0069] This embodiment provides a silicon-carbon composite negative electrode material, which includes a lithium-doped silicon-carbon material core and a perfluorohexanesulfonate lithium coating layer coated on the surface of the core;
[0070] The lithium-doped silicon-carbon material core is a porous structure;
[0071] In the lithium-doped silicon-carbon material core, the doping amount of lithium is 3wt%;
[0072] The thickness of the lithium sulfonate coating layer is 300 nm.
[0073] This embodiment also provides a method for preparing the above silicon-carbon composite negative electrode material, the preparation method comprising the following steps:
[0074] (1) 100 g of phenolic compound and 150 g of aldehyde compound were added to 5000 g of ethanol and dispersed evenly to obtain a solution with a mass fraction of 5 wt%, and then 3 g of template and 3 g of heteroatom compound were added and mixed, and then transferred to a high-pressure reactor at 200 ° C for 8 h of reaction, filtered, and then the obtained filter residue was heated to 650 ° C for 3 h of activation, and carbon dioxide gas was introduced at a flow rate of 100 mL / min. The activated material was carbonized in an argon atmosphere at 1300 ° C for 3 h to obtain a heteroatom-doped porous carbon material;
[0075] The mass ratio of the template agent, the heteroatom compound, the phenolic compound and the aldehyde compound is 3:3:100:150, the template agent is zinc chloride, the heteroatom compound is urea, the phenolic compound is phenol, and the aldehyde compound is formaldehyde;
[0076] (2) The heteroatom-doped porous carbon material is transferred to a tubular furnace, argon gas is introduced to exhaust the air in the tube, and the tube is evacuated to ≤0.1 MPa, and lithium hydride is heated to 900°C to obtain lithium hydride gas, and then lithium hydride gas is introduced into the tubular furnace at a flow rate of 100 mL / min, and the pressure in the furnace is maintained at 0.3 MPa. The introduction time is 120 min, and then trichlorosilane gas is introduced at a flow rate of 300 mL / min for 300 min to obtain a lithium-doped silicon-carbon precursor material;
[0077] (3) 10 g of lithium perfluorohexane sulfonate was added to 200 g of an organic solvent to obtain a lithium sulfonate solution with a mass fraction of 5 wt%, and then 100 g of the lithium-doped silicon-carbon precursor material was added and dispersed evenly, and then spray-dried (inlet temperature of 250 ° C, outlet temperature of 100 ° C, flow rate of 0.5 kg / h, time of 1 h) to obtain a silicon-carbon composite negative electrode material;
[0078] Among them, the mass ratio of lithium-doped silicon-carbon precursor material and lithium perfluorohexane sulfonate is 100:10, and the organic solvent is methyl propionate.
[0079] Example 2
[0080] This embodiment provides a silicon-carbon composite negative electrode material, which includes a lithium-doped silicon-carbon material core and a lithium trifluoromethanesulfonate coating layer coated on the surface of the core;
[0081] The lithium-doped silicon-carbon material core is a porous structure;
[0082] In the lithium-doped silicon-carbon material core, the doping amount of lithium is 1wt%;
[0083] The thickness of the lithium sulfonate coating layer is 50 nm.
[0084] This embodiment also provides a method for preparing the above silicon-carbon composite negative electrode material, the preparation method comprising the following steps:
[0085] (1) 100 g of phenolic compound and 100 g of aldehyde compound were added to 2000 g of ethanol and dispersed uniformly to obtain a solution with a mass fraction of 10 wt%, and then 1 g of template and 1 g of heteroatom compound were added and mixed, and then transferred to a high-pressure reactor at 150 ° C for 12 h of reaction, filtered, and then the obtained filter residue was heated to 500 ° C for 6 h of activation, and carbon dioxide gas was introduced at a flow rate of 50 mL / min. The activated material was carbonized in an argon atmosphere at 1100 ° C for 6 h to obtain a heteroatom-doped porous carbon material;
[0086] The mass ratio of the template agent, the heteroatom compound, the phenolic compound and the aldehyde compound is 1:1:100:100, the template agent is zinc bromide, the heteroatom compound is melamine, the phenolic compound is hydroquinone, and the aldehyde compound is acetaldehyde;
[0087] (2) The heteroatom-doped porous carbon material is transferred to a tubular furnace, argon gas is introduced to exhaust the air in the tube, and the tube is evacuated to ≤0.1 MPa, and lithium hydride is heated to 850°C to obtain lithium hydride gas, and then lithium hydride gas is introduced into the tubular furnace at a flow rate of 50 mL / min, and the pressure in the furnace is maintained at 0.1 MPa for 300 min, and then tetrachlorosilane gas is introduced at a flow rate of 100 mL / min for 600 min to obtain a lithium-doped silicon-carbon precursor material;
[0088] (3) Add 5 g of lithium trifluoromethanesulfonate to 500 g of an organic solvent to obtain a lithium sulfonate solution with a mass fraction of 1 wt%, then add 100 g of the lithium-doped silicon-carbon precursor material and disperse it evenly, and spray dry (inlet temperature of 250 ° C, outlet temperature of 100 ° C, flow rate of 0.5 kg / h, time of 1 h) to obtain a silicon-carbon composite negative electrode material;
[0089] Wherein, the mass ratio of lithium-doped silicon-carbon precursor material to lithium trifluoromethanesulfonate is 100:5, and the organic solvent is ethyl acetate.
[0090] Example 3
[0091] This embodiment provides a silicon-carbon composite negative electrode material, which includes a lithium-doped silicon-carbon material core and a perfluorobutylsulfonate lithium coating layer coated on the surface of the core;
[0092] The lithium-doped silicon-carbon material core is a porous structure;
[0093] In the lithium-doped silicon-carbon material core, the doping amount of lithium is 5wt%;
[0094] The thickness of the lithium sulfonate coating layer is 500 nm.
[0095] This embodiment also provides a method for preparing the above silicon-carbon composite negative electrode material, the preparation method comprising the following steps:
[0096] (1) 100 g of phenolic compound and 200 g of aldehyde compound were added to 30,000 g of ethanol and dispersed uniformly to obtain a solution with a mass fraction of 1 wt%, and then 5 g of template and 5 g of heteroatom compound were added and mixed, and then transferred to a high-pressure reactor at 250 ° C for 6 h of reaction, filtered, and then the obtained filter residue was heated to 800 ° C for 1 h of activation, and carbon dioxide gas was introduced at a flow rate of 200 mL / min. The activated material was carbonized in an argon atmosphere at 1500 ° C for 1 h to obtain a heteroatom-doped porous carbon material;
[0097] The mass ratio of the template agent, the heteroatom compound, the phenolic compound and the aldehyde compound is 1:1:100:100, the template agent is lithium chloride, the heteroatom compound is dopamine, the phenolic compound is catechol, and the aldehyde compound is benzaldehyde;
[0098] (2) The heteroatom-doped porous carbon material is transferred to a tubular furnace, argon gas is introduced to exhaust the air in the tube, and the tube is evacuated to ≤0.1 MPa, and lithium hydride is heated to 950°C to obtain lithium hydride gas, and then lithium hydride gas is introduced into the tubular furnace at a flow rate of 200 mL / min, and the pressure in the furnace is maintained at 0.5 MPa for 30 minutes, and then dichlorosilane gas is introduced at a flow rate of 500 mL / min for 120 minutes to obtain a lithium-doped silicon-carbon precursor material;
[0099] (3) Add 20 g of lithium perfluorobutyl sulfonate to 200 g of an organic solvent to obtain a lithium sulfonate solution with a mass fraction of 10 wt%, then add 100 g of the lithium-doped silicon-carbon precursor material and disperse it evenly, and spray dry (inlet temperature of 250 ° C, outlet temperature of 100 ° C, flow rate of 0.5 kg / h, time of 1 h) to obtain a silicon-carbon composite negative electrode material;
[0100] Among them, the mass ratio of lithium-doped silicon-carbon precursor material and lithium perfluorobutylsulfonate is 100:20, and the organic solvent is diethyl carbonate.
[0101] Example 4
[0102] The difference between this embodiment and embodiment 1 is that no heteroatom compound is added in step (1).
[0103] The rest of the preparation methods and parameters were the same as those in Example 1.
[0104] Example 5
[0105] The difference between this embodiment and embodiment 1 is that no template is added in step (1).
[0106] The rest of the preparation methods and parameters were the same as those in Example 1.
[0107] Example 6
[0108] The difference between this embodiment and embodiment 1 is that the trichlorosilane gas in step (2) is replaced by silane gas.
[0109] The rest of the preparation methods and parameters were the same as those in Example 1.
[0110] Example 7
[0111] The difference between this embodiment and embodiment 1 is that step (1) is not performed, but porous carbon purchased from the market is used (manufacturer: Japan Kuraray Co., Ltd.; model: YP50F; key parameters: specific surface area 1692m 2 / g, particle size 5.6μm).
[0112] The rest of the preparation methods and parameters were the same as those in Example 1.
[0113] Comparative Example 1
[0114] The difference between this comparative example and Example 1 is that the lithium sulfonate coating is not performed, but the amorphous carbon coating is performed, that is, step (3) is replaced by the following steps:
[0115] The lithium-doped silicon-carbon precursor material was transferred to a tubular furnace, argon gas was introduced to expel the air in the tube, and then the temperature was raised to 700°C. Acetylene gas was introduced at a gas flow rate of 100 mL / min for 120 minutes, and then the temperature was lowered in an argon atmosphere to obtain a silicon-carbon composite negative electrode material.
[0116] The rest of the preparation methods and parameters were the same as those in Example 1.
[0117] Figure 1 The DC internal resistance distribution diagram of the soft-pack batteries made of silicon-carbon composite negative electrode materials provided by Examples 1-3, Example 7 and Comparative Example 1 under different SOC states is shown. From the analysis of the diagram, it can be seen that the internal resistance of Examples 1-3 is significantly lower. The reason is that the doping of heteroatoms and metallic lithium in the porous carbon reduces the electronic conductivity of the material, thereby reducing the DCR.
[0118] Comparative Example 2
[0119] The difference between this comparative example and Example 1 is that lithium doping is not performed, that is, lithium hydride gas is not introduced into the tube furnace in step (2).
[0120] The rest of the preparation methods and parameters were the same as those in Example 1.
[0121] Performance Testing
[0122] 1. Physical and chemical properties of the silicon-carbon composite negative electrode materials prepared in the above examples and comparative examples were tested:
[0123] The specific surface area of the silicon-carbon composite negative electrode material was tested in accordance with the national standard GB / T 38823-2020 "Silicon Carbon", and the powder resistivity of the silicon-carbon composite negative electrode material was tested using a four-probe tester, and its gas production was tested (45°C, 48h).
[0124] 2. Button cells were made based on the silicon-carbon composite negative electrode materials provided in the above embodiments and comparative examples, and their electrochemical performance was tested.
[0125] The preparation steps of button cells include:
[0126] The silicon-carbon composite negative electrode material, the binder LA132, the conductive carbon black and the N-methylpyrrolidone were stirred and mixed to obtain a negative electrode slurry; wherein the mass volume ratio of the silicon-carbon composite negative electrode material, the conductive carbon black, the binder LA132 and the N-methylpyrrolidone was 95g:1g:4g:220mL; the negative electrode slurry was coated on a copper foil, and after drying and rolling, a negative electrode sheet was obtained; the electrolyte was LiPF 6 The electrolyte solution has a concentration of 1 mol / L, wherein the solvent is a mixture of ethylene carbonate and diethyl carbonate in a volume ratio of 1:1; the metal lithium sheet is the counter electrode, and the diaphragm is a polypropylene film.
[0127] In an argon glove box, the button cell was assembled on a Blue Power CT2001A battery tester for electrochemical performance testing, with a charge and discharge voltage range of 0.005 V to 2.0 V and a charge and discharge rate of 0.1C.
[0128] In addition, a full-charge expansion test was performed on the negative electrode plate of the button battery. The specific test process is: the thickness D1 of the negative electrode plate of the button battery after rolling is tested, and then the button battery is fully charged to 100% SOC and the negative electrode plate is dissected to measure its full-charge thickness D2, and then the full-charge expansion rate is calculated (full-charge expansion rate = (D2-D1) / D1*100%).
[0129] The above test results are shown in Table 1.
[0130] Table 1
[0131]
[0132] It can be seen from the above table that the present invention not only effectively reduces the irreversible capacity of the silicon-carbon composite negative electrode material, but also improves the electronic conductivity and the first efficiency of the silicon-carbon composite negative electrode material; and, by coating the surface of the inner core with lithium sulfonate, the power performance and the first efficiency of the material are improved, and the gas production is reduced.
[0133] It can be seen from Examples 1 and 4 that if no heteroatom compound is added in step (1), the electronic conductivity of the material increases only slightly, the resistivity of the powder increases, the gas production of the obtained silicon-carbon composite negative electrode material increases, and the performance is weakened.
[0134] It can be seen from Examples 1 and 5 that if no template is added in step (1), it is difficult to form a porous structure, which will lead to a decrease in the electrochemical performance of the material.
[0135] It can be seen from Example 1 and Example 6 that if the trichlorosilane gas is replaced by silane gas, the improvement degree of the gas generation, powder resistivity and full-charge expansion rate of the material becomes worse.
[0136] It can be seen from Example 1 and Example 7 that if porous carbon purchased on the market is used as raw material, it is not conducive to reducing the irreversible capacity of the silicon-carbon composite negative electrode material, the electronic conductivity and initial efficiency of the silicon-carbon composite negative electrode material decrease, and the resistivity and full-charge expansion rate of the powder increase.
[0137] It can be seen from Example 1 and Comparative Example 1 that if amorphous carbon coating is performed instead of lithium sulfonate coating, only the electronic conductivity of the material is slightly improved, but the ionic conductivity and transmission rate of the material are not improved, resulting in a deviation in the power performance of the material.
[0138] It can be seen from Example 1 and Comparative Example 2 that if lithium doping is not performed, it is not conducive to reducing the irreversible capacity of the silicon-carbon composite negative electrode material, and the electronic conductivity and the initial efficiency of the silicon-carbon composite negative electrode material are reduced.
[0139] 2. A soft-pack battery was made based on the silicon-carbon composite negative electrode material provided in the above embodiments and comparative examples, and the rate performance and cycle performance tests were performed.
[0140] The preparation steps of soft pack batteries include:
[0141] The silicon-carbon composite negative electrode material and artificial graphite with a mass ratio of 10:90 are mixed to form the negative electrode sheet, which is then mixed with the positive electrode ternary material (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 ), electrolyte and diaphragm are assembled into a 5Ah soft pack battery; the diaphragm model is Celegard 2400, the electrolyte is LiPF 6Solution (solvent is a mixed solution of ethylene carbonate and diethyl carbonate in a volume ratio of 1:1, LiPF 6 The concentration is 1.3 mol / L).
[0142] The test conditions for rate performance are as follows: the DC resistance (DCR) of the battery charged at room temperature (25°C) at different SOCs (10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%) at 3C.
[0143] Cyclic performance test conditions:
[0144] The charge and discharge voltage range is 2.5-4.2V, the temperature is 25±3.0℃, the charge and discharge rate is 1C / 1C, and the number of cycles is 1000 times.
[0145] The above test results are shown in Table 2.
[0146] Table 2
[0147]
[0148] It can be seen from the above table that the soft-pack battery made of the silicon-carbon composite negative electrode material provided by the present invention has excellent rate performance and cycle performance. The reason is that the silicon-carbon composite negative electrode material provided by the present invention has a low powder resistivity, which reduces the DCR of the battery under different SOC states, that is, improves the fast charging performance of the material; at the same time, the silicon-carbon composite negative electrode material has low full-charge expansion and a high specific surface area, which is conducive to improving the cycle performance of the material.
[0149] The applicant declares that it will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be regarded in all respects as exemplary and non-restrictive, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all changes within the meaning and range of equivalents of the claims be included in the invention. Any reference numeral in a claim should not be regarded as limiting the claim to which it relates.
Claims
1. A method for preparing a silicon-carbon composite negative electrode material, characterized in that: The preparation method comprises the following steps: (1) preparing a carbon material, and then sequentially introducing a lithium source gas and a silicon source gas into a reaction device where the carbon material is located to obtain a lithium-doped silicon-carbon precursor material; (2) mixing the lithium-doped silicon-carbon precursor material, lithium sulfonate and an organic solvent, and drying the mixture to obtain the silicon-carbon composite negative electrode material; The carbon material in step (1) is a heteroatom-doped porous carbon material, and the preparation steps of the heteroatom-doped porous carbon material include: The template, the heteroatom compound, the phenolic compound, the aldehyde compound and the alcohol organic solvent are mixed and reacted, and then activated and carbonized to obtain the heteroatom-doped porous carbon material; The mass ratio of the template, the heteroatom compound, the phenolic compound and the aldehyde compound is (1-5):(1-5):100:(100-200); The reaction temperature is 150-250°C and the reaction time is 6-12h; The activation temperature is 500-700°C and the activation time is 1-6h; The carbonization treatment temperature is 1100-1500°C and the time is 1-6h; The silicon-carbon composite negative electrode material comprises a lithium-doped silicon-carbon material core and a coating layer coated on the surface of the core, wherein the material of the coating layer is lithium sulfonate; In the lithium-doped silicon-carbon material core, the doping amount of lithium is 1-5wt%; The lithium-doped silicon-carbon material core is further doped with heteroatoms, wherein the heteroatoms are nitrogen atoms; The lithium sulfonate is any one of lithium trifluoromethanesulfonate and lithium dodecanesulfonate or a combination of the two.
2. The preparation method according to claim 1, characterized in that: The coating layer has a thickness of 50-500 nm.
3. The preparation method according to claim 1, characterized in that: The template comprises any one of zinc chloride, zinc bromide, lithium chloride or lithium bromide or a combination of at least two thereof; The heteroatom compound includes any one of urea, melamine or dopamine, or a combination of at least two thereof; During the activation process, carbon dioxide gas is introduced; The atmosphere of the carbonization treatment is an inert atmosphere.
4. The preparation method according to claim 1, characterized in that: The lithium source gas in step (1) includes lithium hydride gas; The flow rate of the lithium source gas in step (1) is 50-200 mL / min; The lithium source gas is introduced into the reactor for 30-300 min. The silicon source gas in step (1) is chlorosilane gas; The chlorosilane gas includes any one of trichlorosilane, tetrachlorosilane, dichlorosilane, methyldichlorosilane, methylchlorosilane, tripropylchlorosilane, dimethylchlorosilane or propyltrichlorosilane gas, or a combination of at least two thereof; The flow rate of the silicon source gas in step (1) is 100-500 mL / min; The silicon source gas is introduced into the step (1) for 120-600 minutes.
5. The preparation method according to claim 1, characterized in that: The mass ratio of the lithium-doped silicon-carbon precursor material to lithium sulfonate in step (2) is 100:(5-20); The specific steps of mixing in step (2) include: Adding lithium sulfonate to an organic solvent to obtain a lithium sulfonate solution, and then adding a lithium-doped silicon-carbon precursor material to mix; The organic solvent comprises any one or a combination of at least two of methyl propionate, ethyl acetate, diethyl carbonate, ethyl methyl carbonate or dimethyl carbonate; The mass fraction of the lithium sulfonate solution is 1-10wt%; The drying method includes spray drying.
6. The preparation method according to claim 1, characterized in that: The preparation method comprises the following steps: (1) adding a phenolic compound and an aldehyde compound to an alcohol organic solvent and dispersing them uniformly to obtain a solution with a mass fraction of 1-10 wt%, then adding a template and a heteroatom compound to mix, and then transferring to a high-pressure reactor at 150-250° C. for 6-12 hours of reaction, filtering, and then activating the obtained filter residue at a temperature of 500-700° C. for 1-6 hours, while introducing carbon dioxide gas at a flow rate of 50-200 mL / min, and after activation, carbonizing in an inert atmosphere at 1100-1500° C. for 1-6 hours to obtain a heteroatom-doped porous carbon material; Wherein, the mass ratio of the template agent, the heteroatom compound, the phenolic compound and the aldehyde compound is (1-5):(1-5):100:(100-200); (2) transferring the heteroatom-doped porous carbon material to a tube furnace, evacuating the furnace, and then introducing a lithium source gas at a flow rate of 50-200 mL / min, and maintaining the pressure in the furnace at 0.1-0.5 MPa for 30-300 min, and then changing to a silicon source gas at a flow rate of 100-500 mL / min for 120-600 min to obtain a lithium-doped silicon-carbon precursor material; (3) adding lithium sulfonate to an organic solvent to obtain a lithium sulfonate solution with a mass fraction of 1-10 wt%, then adding the lithium-doped silicon-carbon precursor material to disperse uniformly, and spray drying to obtain a silicon-carbon composite negative electrode material; Wherein, the mass ratio of lithium-doped silicon-carbon precursor material to lithium sulfonate is 100:(5-20).
7. A negative electrode plate, characterized in that: The negative electrode plate includes a silicon-carbon composite negative electrode material prepared by the preparation method according to claim 1.
8. A lithium ion battery, comprising the negative electrode sheet according to claim 7.
Citation Information
Patent Citations
Nitrogen-doped porous carbon material for lithium-air battery positive electrode
CN103855366A
Negative electrode material, preparation method, negative electrode slurry, negative electrode pole piece and battery
CN117878290A
Lithium-doped silicon-carbon composite material and preparation method thereof
CN118213516A
Negative-electrode material for secondary battery, and secondary battery
WO2023190239A1